(3COH GdcGJHs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3bGd CHh eMeO Hf bJjHI (B: (3CeG HYO MeO Gddg HLejY eMGeOg hGdKfGA Ydjg aEfG QCjJ CcKQ Cgd ReGffG Yf SHjd GdCOH fGcHjf s
(3BNQgG (B:s
(3hEfeG LF HgPG GdeUOQ eNGdaI ddCaYGd dCf GdCaYGd hEf GNJdaJ CHfjJgG hGMOI ai GdeYfi Ef TGA Gddg s
(3GdfSNI YdjgG TQhM hJUMjMGJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
Keywords: (3GdCOHs